Resgate das técnicas construtivas e a importância dos materiais remanescentes das argamassas utilizadas nas confecções das paredes de barro e dos revestimentos das edificações históricas - uma abordagem epistêmica - Fernando Roberto de Castro Veado (2008)
This study includes a reflection on the coatings preservation and restoration problem, that arebuilt structure fundamental elements, because besides having a protective function, they also own, many times, na important ornamental function. Being thus, time testimony and of the past, this ones layers and the constructives techniques must be preserved, because the historical monuments cant be visas just as on old and damaging building that was habitation of some character, or the one that is marked for historical happening, but also, know of the existing materials importance in the built structure and the way of her applications, with the techniqueseach region, post that was used of primitive or limited techniques. Thus, to the historical monuments restorer and conservative, fits consolidate the work how much possible and make it returns to her origin state, using of all the techniques of restore and of the historical research that must propitiate the constructive process knowledge, of the interventions, of the eventual anomalies detection, because the respect to the well restored the constituent materials authenticity and of the constructive techniques is just that are going to keep the distinct times historical value. It is important to point out that the methods employees for the preservation and restore of the techniques and of the coatings vary as deterioration the kind and the necessary materials for your preservation. Thus, it is necessary, in any work of restore, a coatings preservation state discerning previous analysis, of the techniques and that this action be accomplished with conscience and responsibility than is doing and of the thing value on top of wich are working. Otherwise, they can provoke more serious pathologies than the previously found. The objective of this study is to describe the knowledge in this area maid in the mining architecture. It does also a main anomalies compilation found in the mud walls and of the existing materials, of form to contribute for a interventions improvement of restore.